Reducing non-radiative voltage losses in organic solar cells using molecular encapsulation. (19th January 2023) - Sharma, Anirudh; Sharma, Lisa; Bertrandie, Jules; Villalva, Diego R.; Gao, Yajun; De Castro, Catherine S. P.; Troughton, Joel; Gorenflot, Julien; Laquai, Frederic; Bronstein, Hugo; Baran, Derya
Abstract : Molecular encapsulation is a promising strategy to reduce non-radiative losses and enhance stability of organic solar cells, via reduced aggregation in the polymer phase. Encapsulated polymers demonstrated enhanced electroluminescence and better donor–acceptor intermixing. Abstract : Non-radiative voltage loss is one of the significant bottlenecks limiting the performance of organic solar cells (OSCs). This work presents a material design approach for conjugated polymers isolating the polymer chains with molecular encapsulation, enabling better control over the donor–acceptor spacing. Bulk-heterojunction OSCs based on encapsulated polymers as electron donors show a remarkable increase of ∼50 mV in the V oc . Significant improvement in the V oc is attributed to reduced non-radiative voltage losses as evidenced by enhanced electroluminescence as a result of suppressed intermolecular aggregation and an increase in structural disorder. Importantly, molecular encapsulation resulted in notable improvement in the operational stability of OSCs with no burn-in loss in V oc, presenting a promising strategy to simultaneously enhance the performance and operational stability of OSCs.